Determinants of Stunting Among Under-Five Children (0–59 Months) in Central Sulawesi Province - Bamba, Marchell; Sudaryo, Mondastri Korib; Djuwita, Ratna; Umniyati, Helwiah (UI Scholars Hub, 2026)
Stunting is caused by chronic malnutrition which can be caused by various factors including poverty, poor nutritional intake and maternal health, and inappropriate infant feeding. This study was conducted to determine what factors cause stunting in Central Sulawesi Province. This study was conducted using a cross-sectional observational analysis method using secondary data from the Survei Kesehatan Indonesia (SKI) 2023. The analysis was carried out using logistic regression. The sample used was 2179 respondents. The dependent variable is stunting while the independent variables are age, gender, area of residence, gestational age, provision of PMT, exclusive breastfeeding, maternal occupation, maternal education, and the number of family members in the household. Based on the data obtained, the prevalence of stunting in Central Sulawesi Province is 24.42%. In the multivariate analysis, the factors that had a significant relationship were: age variable (P value Keywords: Stunting, Risk factor, Central Sulawesi